2007
DOI: 10.1007/s00223-007-9031-3
|View full text |Cite
|
Sign up to set email alerts
|

Damaging Fatigue Loading Stimulates Increases in Periosteal Vascularity at Sites of Bone Formation in the Rat Ulna

Abstract: Bone formation in a variety of contexts depends on angiogenesis, however there are few reports of the vascular response to osteogenic skeletal loading. We used the rat forelimb compression model to characterize vascular changes after fatigue loading. The right forelimbs of 72 adult rats were loaded cyclically in vivo to one of four displacement levels, to produce four discrete levels of ulnar damage. Rats were euthanized 3-14 days after loading and their vasculature perfused with silicone rubber. Transverse hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 40 publications
5
36
2
Order By: Relevance
“…In the current study, we showed an early angiogenic response following WBF loading, including upregulation of Vegf and Hif1a within 1 hour, consistent with previous reports of early Vegf expression [12-13]. By day 3, there was a significant increase in vascularity in the region where woven bone was starting to form, consistent with a previous study [32]. Because the healing response in this model is characterized by non-endochondral bone formation [28], it differs from fracture healing and DO, which include both non-endochondral and endochondral bone formation [20, 49].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, we showed an early angiogenic response following WBF loading, including upregulation of Vegf and Hif1a within 1 hour, consistent with previous reports of early Vegf expression [12-13]. By day 3, there was a significant increase in vascularity in the region where woven bone was starting to form, consistent with a previous study [32]. Because the healing response in this model is characterized by non-endochondral bone formation [28], it differs from fracture healing and DO, which include both non-endochondral and endochondral bone formation [20, 49].…”
Section: Discussionsupporting
confidence: 92%
“…Second, the number of loading cycles is variable in the WBF loading model ranging from 469 to 23463 (4-195 minutes). This variability in cycle number has been well documented in this loading model [11-12, 28, 32, 56] and was not correlated with any of our experimental outcomes. Third, one consideration in our WBF loading scenario is the formation of lamellar bone that occurs adjacent to woven bone.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This situation differs from the exogenous mechanical stimuli implemented in the current study, which are not associated with significant hypoxia or increased angiogenesis (45), but rather, are considered anabolic. On the other hand, application of much more intensive loads that induce bone fatigue with significant tissue damage is associated with increased skeletal vascularity likely due to tissue hypoxia (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Robust expression of HIF-1α has been observed in the inflammatory cells located in the expanded periosteal region as soon as 1 day after loading, with a peak in gene expression at day 7 [22, 25]. Additionally, woven bone formation after stress fracture is preceded by increased periosteal vascularity [25, 26] and is impaired by angiogenic inhibition [27]. In contrast to fatigue loading, mechanical loading applied near physiological strain levels for fewer cycles does not produce damage, and stimulates lamellar bone formation.…”
Section: Introductionmentioning
confidence: 99%